Supply Chain Management - a Contemporary Concept of Cooperative Competitiveness Development - Zekić, Zdravko (Oeconomica Jadertina, 2018)
Dynamic technology development and fast-changing consumer preferences in a modern globalized market weaken the competitive potentials of individual companies for a competitive battle with organized strategic chains of advanced supply chain management. Process optimization requirements force independent companies to focus solely on those activities where they are most competitive and link their value chains to partners supply chains, from raw material to final consumer, in order to maximize efficiency and effectiveness of the process and achieve competitive advantage on the market. Supply Chain Management becomes a modern concept of corporate success management through the development of a new model of cooperative competitiveness. The already present future proves that companies are less competitive on the markets; the competitive rivalry is increasingly taking place between supply chains. The purpose of this paper is to point to the trends and bases of the Supply Chain Management concept development as a fundamental factor for success of modern business systems that gain competitive advantage in recent markets.